The ILMU PEMERINTAHAN DALAM PRAKTEK : PERSPEKTIF EROFA KONTINENTAL: Ilmu Pemerintahan Eropa Kontinental - Utang Suwaryo (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2021)
Problems and phenomenon of government have existed for thousands of years,because the existence of the government is an indisputable empirical system and is a human need. In government is a regulation of the relationship between the ruler and the governed, so that order, security, prosperity, and justice can be realized. Government science as a scientific idea has actually appeared since 1822 in The United State, namely with the publication of The Introduction to The Science of Government Written For The Youth of United State. Likewise in 1876 SV Blakeslee wrote about Archology or The Science of Government. Actually the existence of government science in the future depends on the extent to which the activities,creativity and productivity of government scientists in examining existing empirical phenomena so that they can form new theories. The emergence of The Continental European Schools and Anglo Saxon basically, because they actively observe the existing phenomena so that they are able to produce a paradigm. In simple terms, we can also see the phenomenon of indigenous government that is around us, the phenomenon of governance that is prevailing and embraced by various groups of nation today (contemporary government), we can even see the phenomenon of global government.